2017
DOI: 10.1016/j.cose.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

“Security begins at home”: Determinants of home computer and mobile device security behavior

Abstract: He holds MSc and PhD degrees and works in the area of Computer Security and Information Systems. His research interests include affective computing, human-computer interaction and information security. Xuequn (Alex) Wang is a Lecturer in Murdoch University. He received his Ph.D. in Information Systems from Washington State University. His research interests include knowledge management, online communities, and idea generation. His research has appeared (or is forthcoming) in Communications of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 60 publications
3
57
1
2
Order By: Relevance
“…When faced with a breach, it is common practice for businesses to request users to reset passwords for all the other accounts where that account information is used (UnderArmour, 2018). Previous research on security behaviors has found support for perceived vulnerability and perceived severity (Chenoweth et al, 2009;Crossler & Belanger, 2014;Liang & Xue, 2010;Martens et al, 2019;Thompson et al, 2017). Therefore, we hypothesize H2: Perceived severity of password loss will be positively related to intention to use password managers.…”
Section: Background and Hypothesesmentioning
confidence: 86%
See 1 more Smart Citation
“…When faced with a breach, it is common practice for businesses to request users to reset passwords for all the other accounts where that account information is used (UnderArmour, 2018). Previous research on security behaviors has found support for perceived vulnerability and perceived severity (Chenoweth et al, 2009;Crossler & Belanger, 2014;Liang & Xue, 2010;Martens et al, 2019;Thompson et al, 2017). Therefore, we hypothesize H2: Perceived severity of password loss will be positively related to intention to use password managers.…”
Section: Background and Hypothesesmentioning
confidence: 86%
“…In these cases, the use of antivirus reduces the chance that computing resources are compromised. Previous research has used protective motivation theory (PMT) to explain individuals' intention to use such security tools (Chenoweth, Minch, & Gattiker, 2009;Gurung, Luo, & Liao, 2009;Martens, De Wolf, & De Marez, 2019;Thompson, McGill, & Wang, 2017).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Two findings from these works are especially relevant to our study: First, Thompson et al [33] hypothesize that vendor representatives and other security experts may be able to support positive behavior change. We empirically explore this theory through our sales staff interviews.…”
Section: A Security Behavior Adoption Among Home Usersmentioning
confidence: 91%
“…The same researchers consider similar symptoms that occur during a long time spent on mobile phones [11]. The work of N. Thompson, T. McGill, X. Wang [12] is devoted to the features of the personal perception of the level of security of working with various personal means of information and communication interaction, in particular, with mobile devices and personal computers. ---…”
Section: Methodsmentioning
confidence: 99%